Risk aversion under preference uncertainty - Roman Kräussl; André Lucas; Arjen Siegmann (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
We show that if an agent is uncertain about the precise form of his utility function, his actual relative risk aversion may depend on wealth even if he knows his utility function lies in the class of constant relative risk aversion (CRRA) utility functions. We illustrate the consequences of this result for asset allocation: poor agents that are uncertain about their risk aversion parameter invest less in risky assets than wealthy investors with identical risk aversion uncertainty.
urn:nbn:de:hebis:30-87127
Keywords: D81; D84; G11; 330; Risk Aversion; Preference Uncertainty; Risk-taking; Asset Allocation